2016
DOI: 10.1590/0037-8682-0169-2016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with Chlamydia trachomatis infection among women with HIV in São Paulo

Abstract: Introduction: This study aimed to estimate the prevalence and risk factors associated with Chlamydia trachomatis (CT) infection among women with HIV in São Paulo. Methods: This cross-sectional study included women with HIV who were receiving care from sixteen public health services in São Paulo (October 2013 to March 2014). All participants answered a questionnaire regarding their sociodemographic, behavioral, and clinical characteristics. A urine sample was tested for CT and Neisseria gonorrhoeae (NG) using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
2
1
2
Order By: Relevance
“…public health system patients in hospitals or university clinics), while the majority have been conducted targeting specific groups of patients, such as only HIV patients, pregnant women, and young people. 5,8,1725 The CT and NG infection prevalence identified in the present study is in concordance with those reported by the Brazilian Ministry of Health. 4 Our sample reflected the most varied population types, since it was drawn from a reference center for women seeking various types of care: routine examinations, STI treatment, antenatal care, etc.…”
Section: Discussionsupporting
confidence: 91%
“…public health system patients in hospitals or university clinics), while the majority have been conducted targeting specific groups of patients, such as only HIV patients, pregnant women, and young people. 5,8,1725 The CT and NG infection prevalence identified in the present study is in concordance with those reported by the Brazilian Ministry of Health. 4 Our sample reflected the most varied population types, since it was drawn from a reference center for women seeking various types of care: routine examinations, STI treatment, antenatal care, etc.…”
Section: Discussionsupporting
confidence: 91%
“…In Rwanda, the IgG prevalence of C. trachomatis antibodies was 18.8% in subfertile and 18.3% fertile and IgA prevalence rates of 7.4% in sub-fertile and 4.1% in the fertile women lower than in our report [31]. The disproportionate burden of C. trachomatis infection in most studies might be attributed to unsafe sociobehavioural characteristics of the study population in addition to the choice of the diagnostic technique with the sero-diagnosis yielding higher prevalence due to crossreactivity than the molecular technique which more accurate [33,35].…”
Section: Prevalence Of C Trachomatis Among Cases and Controlscontrasting
confidence: 61%
“…Si bien éste presenta una sensibilidad ligeramente inferior si se compara con el hisopado cervical o vaginal (27) , el mismo es un método no invasivo, aceptable para el diagnóstico de infecciones genitales por C. trachomatis y es comúnmente usado como técnica de screening durante el embarazo. El porcentaje de resultados inválidos encontrados en nuestro estudio, 0,57%, fue menor al hallado en otros realizados en Brasil del 3,7% (28) y en España del 4,4% (21).…”
Section: Discussionunclassified